In-Kind Transfers and Work Incentives - Leonesio, Michael V. (Journal of Labor Economics, 1988)
Recent developments in rationing theory are used to examine the differences between the effects of in-kind and cash transfers on labor supply. It is not possible to tell a priori which type of transfer will cause the greater reduction in hours of work; the answer depends on the extent to which in-kind transfers distort consumption choices and on the relationship between the transferred commodities and leisure. Hicks-Allen complements can cause greater reductions in labor supply than equally generous cash transfers, while strong Hicks-Allen substitutes can induce increases in market work.